Age-Standardized Mortality of Persons on Probation, in Jail, or in State Prison and the General Population, 2001-2012. (November 2019) - Wildeman, Christopher; Goldman, Alyssa W.; Wang, Emily A.
Objectives: The number of adults in the United States being held on probation—persons convicted of crimes and serving their sentence in the community rather than in a correctional facility—approached 4 million at the end of 2016 and continues to grow, yet little is known about the health and well-being of this population. We compared the standardized mortality ratios of persons on probation in the United States with persons in jail, persons in state prison, and the general US population. Methods: We used administrative data from 2001-2012 from the Bureau of Justice Statistics and the Centers for Disease Control and Prevention WONDER database and indirect standardization techniques to compare the mortality rates of persons on probation in 15 states with the mortality rates of persons in jail, persons in state prison, and the general US population. We applied the age-specific mortality rates of 3 populations (general US population, persons in jail, and persons in state prison) to the age distribution of persons on probation to estimate standardized mortality ratios. Results: Persons on probation died at a rate 3.42 times higher than persons in jail, 2.81 times higher than persons in state prison, and 2.10 times higher than the general US population, after standardizing the age distribution of persons on probation relative to the other 3 groups. Conclusions: Public health interventions should target persons on probation, who have received less attention from the public health community than persons serving sentences in jails and prisons.